Single‐cell profiling of transcriptomic changes during in vitro maturation of human oocytes - Hiroki Takeuchi; Mari Yamamoto; Megumi Fukui; Akihiro Inoue; Tadashi Maezawa; Mikiko Nishioka; Eiji Kondo; Tomoaki Ikeda; Kazuya Matsumoto; Kei Miyamoto (Reproductive Medicine and Biology, 2022)
Abstract Purpose In vitro maturation (IVM) of human oocytes offers an invaluable opportunity for infertility treatment. However, in vitro matured oocytes often show lower developmental abilities than their in vivo counterparts, and molecular mechanisms underlying successful maturation remain unclear. In this study, we investigated gene expression profiles of in vitro matured oocytes at the single‐cell level to gain mechanistic insight into IVM of human oocytes. Methods Human oocytes were retrieved by follicular puncture and in vitro matured. In total, 19 oocytes from 11 patients were collected and subjected to single‐cell RNA‐seq analyses. Results Global gene expression profiles were similar among oocytes at the same maturation stage, while a small number of oocytes showed distinct transcriptomes from those at the corresponding maturation stage. Differential gene expression analysis identified hundreds of transcripts that dynamically altered their expression during IVM, and we revealed molecular pathways and upstream regulators that may govern oocyte maturation. Furthermore, oocytes that were delayed in their maturation showed distinct transcriptomes. Finally, we identified genes whose transcripts were enriched in each stage of oocyte maturation. Conclusions Our work uncovers transcriptomic changes during human oocyte IVM and the differential gene expression profile of each oocyte.